FONDASI UNTUK PENDIDIKAN ISLAM MULTIKULTURAL DI INDONESIA: ANALISIS Q.S. AL-á¸¤UJURÄ€T [49]: 11-13 DALAM TAFSIR MARÄ€á¸¤ LABÄªD, TAFSIR AL-AZHAR, DAN TAFSIR AL-MISHBÃ‚H - Ahmad Darmadji (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
This article is intended for developing the foundation of multicultural Islamic education in accordance with the identity of Indonesia nation. This article reviewed the meaning contained in Q.S. Al-Hujarat (49): (11-13), often related to groups of verses proposing the multicultural spirit in a life. These verses were then examined by refering to the comprehension of Indonesia tafseer expert in Tafseer Marah Labid, Tafseer Al-Azhar, and Tafseer Al-Mishbah. Those three tafseers composed by Indonesian authors are expected to be able to represent the peculiarity of Islamic experience in Indonesia. the result of the discussion towards the meaning of the verses indicated that the multicultural spirit was recognized as an important part in dynamics of the teachings of Islamic since it is inevitability. If it is associated with the multicultural education, the spirit of teachings of Alquran needs to be developed by reinforcing multicultural visions in Islamic education in Indonesia, begun with the content and the development of government policy.